A Facile and Efficient Reaction of Aromatic Aldehydes with the Isocyanide- Dialkylacetylenedicarboxylate Zwitter Ions: Formation of 2-Amino-5-aryl Furan Derivatives - Asghari, Sakineh; Qandalee, Mohammad (Asian Journal of Chemistry, 2010)
The 1:1 intermediate generated by the addition of t-butyl isocyanide to dialkyl acetylene dicarboxylate is trapped by various aromatic aldehydes to yield 2-amino-5-aryl furan derivatives.